Osteoporosis and Bone Densitometry Measurements - Guglielmi, Giuseppe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Osteoporosis is a serious problem worldwide, and its significance is continuing to increase as the world population grows and ages. Osteoporosis and Bone Densitometry Measurements provides a comprehensive review of the latest research on this potentially devastating condition. The book encompasses prevention, diagnosis, and therapy, providing state of the art information on each aspect. A wide range of topics are discussed, including differentiation between acute and chronic, benign and malignant vertebral fractures; the value of the WHO FRAX tool in patient evaluation; the roles of dual-energy X-ray absorptiometry, quantitative computed tomography, quantitative ultrasound, and high-resolution imaging; and the use of kyphoplasty and vertebroplasty to treat vertebral compression fractures. All chapters are written by acknowledged experts in the field.
Osteoporosis: Epidemiology -- Radiographs in Osteoporosis -- Insufficiency Fractures -- Identification of Vertebral Fractures -- Benign vertebral fracture: acute vs. chronic -- Malignant vertebral fracture: acute vs. chronic -- The use of FRAX in the evaluation of patients with osteoporosis -- Axial and Peripheral DXA -- Axial and Peripheral QCT -- Quantitative US and fracture risk -- High Resolution Imaging -- Pediatric Bone Densitometry -- Kyphoplasty and Vertebroplasty in Osteoporosis -- Quality assurance and Dosimetry in Bone Densitometry.
Keywords: Medicine; Geriatrics; Radiology, Medical; Interventional radiology; Endocrinology; Metabolic diseases; Medicine & Public Health; Imaging / Radiology; Geriatrics/Gerontology.; Diagnostic Radiology; Interventional Radiology; Endocrinology; Metabolic Diseases